2011
DOI: 10.1200/jco.2011.29.4_suppl.269
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of the monoclonal antibody FG-3019 to connective tissue growth factor (CTGF) in locally advanced or metastatic pancreatic cancer.

Abstract: 269 Background: CTGF is highly expressed in pancreatic tumors and is thought to mediate local desmoplasia. FG-3019 is a fully human monoclonal antibody against CTGF. Studies using FG-3019 in murine xenograft models have shown reduced tumor growth and metastasis. Methods: This open-label, dose escalation study assessed the safety and pharmacokinetics of FG-3019 (3, 10, 15, and 25 mg/kg q14D). FG-3019 was initiated on D1 to assess single-agent toxicity. Standard gemcitabine and erlotinib were added on D15. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…CTGF deregulation acts to increase tumour angiogenesis in tumours over‐ and underexpressing CTGF compared to normal cell counterparts. CTGF increased tumour angiogenesis in vivo in breast cancer, glioblastoma multiforme and pancreatic cancer . In all these cancer types, CTGF is over expressed compared to normal cells.…”
Section: Mechanisms Of Ctgf Action In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…CTGF deregulation acts to increase tumour angiogenesis in tumours over‐ and underexpressing CTGF compared to normal cell counterparts. CTGF increased tumour angiogenesis in vivo in breast cancer, glioblastoma multiforme and pancreatic cancer . In all these cancer types, CTGF is over expressed compared to normal cells.…”
Section: Mechanisms Of Ctgf Action In Cancermentioning
confidence: 99%
“…In a pancreatic mouse flank‐tumour model, a CTGF monoclonal antibody (FG‐3019, Fibrogen, San Francisco, CA) reduced tumour growth . In humans, a Phase 1 clinical trial of FG‐3019 was used in locally advanced or metastatic pancreatic cancer patients and was well tolerated . Recently in pancreatic cancer, Neesse et al found in vivo that gemcitabine delivered alongside FG‐3019 increased tumour cell death without altering gemcitabine delivery, reported to be due to FG‐3019 disrupting the survival signal x‐linked inhibitor of apoptosis protein ( XIAP ).…”
Section: Mechanisms Of Ctgf Action In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…FG-3019 has been evaluated in several phase 1 clinical studies in patients with diabetic kidney diseases [35], idiopathic lung fibrosis and pancreatic cancer and is currently in phase 2 testing in idiopathic lung fibrosis (NCT01262001) and chronic hepatitis B infection-related liver fibrosis (NCT01217632). The phase 1 study of FG-3019 in combination with Gemcitabine and Erlotinib in patients with advanced pancreatic cancer (NCT01181245) has completed patient enrollment, and results of interim analysis demonstrated impressive PET responses at the highest dose in some patients [36]. It is noteworthy, that at least in pancreatic cancer, CTGF is expressed not only in the cancer cells, but also in the tumor stroma and is most abundant in pancreatic stellate cells within the stroma [37].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental drug was administered combination with Erlotinib and Gemcitabine; no toxicity was found relating to FG-3019. Patients progressed after a median time of 3.7 months and had a median survival of 9.4 months [ 110 ]. FG-3019 has been tested previously in a phase I study in patients with microalbuminuric diabetic kidney disease.…”
Section: New Approaches To Target Ccn Proteins In Hccmentioning
confidence: 99%